The role of legal reform in the system of legal protection. (Journal of actual problems of jurisprudence, 2016)
This article examines the role of law reform in the system of legal protection. The Concept of Legal Policy of the Republic of Kazakhstan for the period 2010 to 2020 were the main directions of development of the legal system and legal advocacy conducted meet the needs of the people and enhance the quality of judicial work.
Keywords: rule of law; law enforcement; public order; political stability; laws; legal policy